Use of compost in agroforestales plantation in the center of forestry research Macuya, Ucayali, 2010 - Chota-Isuiza, Marco A. (2019)
This work had as objective to install agroforestry plantations using different levels of compost as environmental education practice by students of the National University of Ucayali in the center of Forestry Research-Macuya , and compare the effect of compost treatments plantation T1, T2 and T3 with respect to planting To (witness or control that has no compost); to determine the level of knowledge of environmental education in the students of the Faculty of Education and the Faculty of Forestry and Environmental Sciences. It was conducted in two stages: rst it was tested the pretest, n = 137; of a total population of 900 students, it was not taught any knowledge; an average grade of X = 8.08 was found; in the posttest where they received knowledge about environmental education, an average note of X = 13.94 was found. In the second stage, the students prepared the ground for planting agroforestry in an extension 1 Ha in the Center of Forestry Research-Macuya, which was divided into 4 areas of 2,500 m2 each, in which it was installed the plantations T1 (9.8 N compost); T2 (19.6 N compost); T3 (29.4 N compost) and planting To (witness or control that has no compost). The results were the following: Good level of knowledge about environmental education and installation of agroforestry plantations using different levels of compost as the practice of environmental education. The average of plantation T1 planting was higher than the averages of the plantations; T2, T3 and to. In the hypothesis test, agroforestry plantations T1; T2 and T3 there is no signicance with respect to To.